Economic development on Madura Island through halal tourism: A business feasibility study - Zakik Zakik; Ahmad Kamil; Alvin Sugeng Prasetyo; Muhamad Nafik Hadi Ryandono; Ida Wijayanti (Universitas Negeri Surabaya, 2022)
The main objective of this research is to analyze the business feasibility of a halal tourism destination in Madura, exclusively Lon Malang Beach. The analysis includes technical, social economic, and financial feasibility study. The financial analytical method used in this study is Investment Feasibility Analysis includes Payback Period (PP), Net Present Value (NPV), and Benefit Cost Ratio (BCR). The investment feasibility analysis is used to determine the level of return-on-investment alternatives, assess investment alternatives, and determine priorities for investment, thus avoiding investments that only waste resources. The measurement results show that the Payback Period (PP) is in the 9th year, which means that in 9 years, this project will have a return on investment. NPV values greater than 0 and BCR of more than 2 indicate that the Lon Malang tourism development project is feasible. This research is the first research to bring ideas about a feasibility study in halal tourism sectors. This research enriches the knowledge and research on feasibility studies of halal tourism sectors. This research is said to bring important information in decision-making, especially to improve the business and guide the decision-making of investors and government parties, especially in Madura Regency.